Afro‐Catholicism in Latin America. Issue 5 (16th April 2019) - Selka, Stephen
Abstract: This article provides a historical and ethnographic overview of Afro‐Catholicism in Latin America. For the purposes of this article, "Afro‐Catholicism" encompasses the wide variety of ways that people of African descent have practiced or engaged with Catholicism. Much of the article focuses on Brazil, but it also draws on the literature on Afro‐Catholicism in Haiti and Cuba both to highlight similarities and differences throughout Latin America and to foreground the necessarily transnational scope of this topic.